POST- NATAL PAIN AND THE RELATIONSHIP BETWEEN SOME FACTORS AND SEVERITY OF PAIN (Vietnam Journal of Community Medicine, 2021)
Objective: (1) To describe about pain among post-natal mothers, (2) To learn about the relationship between some factors and severity of pain. A longitudinal studies was conducted on a group of 206 post-natal mothers at the Department of Obstetrics at  National Hospital of Obstetrics and Gynecology. Results: 85% of mothers got pain score at 4 or more. The factors of type of delivery (vaginal or cesarean delivery), breast feeding are related to the severity of pain among mothers. Epidural analgesia during vaginal delivery or after cesarean delivery are related to the severity of pain among mothers in vaginal delivery group and cesarean delivery group.Conclusion: The rate of post-natal mothers needing pain relief is high. The factors of type of delivery (vaginal or cesarean delivery), breast feeding are related to the severity of pain among mothers. Epidural analgesia during vaginal delivery or after cesarean delivery are related to the severity of pain among mothers in vaginal delivery group and cesarean delivery group
Keywords: Post – natal pain, post – natal mother